Experimental Methods: ISBN 978-606-95069-8-1 - & Dr. BENOUDJAFER Ibtissam, Dr. BENOUDJAFER Imane (Technium Books, 2024)
BENOUDJAFER Imane, BENOUDJAFER Ibtissam , Experimental Methods; ISBN 978-606-95069-8-1, TECHNIUM PRESS, 2024. Ministry Of Higher Education and Scientific Research The University of TAHRI Mohamed Béchar Faculty of technology Department of civil engineering and hydraulics __________________________________________________ Pedagogical Course Handout Title: " Experimental Methods" Subject Code: MGCD621 Level: Master (S2) Field of study: Civil Engineering Specialty: Civil Engineering ________________________________ Prepared by the teacher: Dr. BENOUDJAFER Imane & Dr. BENOUDJAFER Ibtissam